Disharmony in the Establishment of the Merah Putih Village Cooperative from the Perspective of Cooperative Principles - Mardiana, Yusni Fitri; Dewantara, Reka; Wisnuwardhani, Diah Aju (International Journal of Business, Law, and Education, 2025)
The process of establishing the Merah Putih Village Cooperative, carried out through village government policy, raised normative issues, especially regarding the fulfillment of the principle of voluntary membership as stipulated in Law Number 25 of 1992 concerning Cooperatives. This study aims to examine the alignment between the cooperative establishment model influenced by government policy intervention and the principle of free will in the legal act of establishing a cooperative. The approach used is normative legal research based on legislation analysis, legal concepts, and historical perspectives to examine the normative structure related to principles in the process of establishing cooperatives at the village level. The results of this study are expected to contribute to the proper application of legal principles, ensuring that the establishment of cooperatives is legally legitimate in accordance with applicable laws and regulations.